ESBL PREVALANCE IN URINE SPECIMENSOF CANCER PATIENTS AT A TERTIARY CARE CANCER CENTRE IN KERALA - SAMUEL, SAJANI; Vismaya; Rudrapathy, Parthiban; Murugesan, Saravanan; KE, Sarath (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study documents the prevalence of extended-spectrum beta-lactamase (ESBL)-producing multiple drug resistance uropathogens reported prospectively for a period of 3 months from February 2020 to April 2020 and its susceptibility to the commonly recommended antibiotics for urinary tract infections (UTI). Methods: Identification and characterization of the uro-pathogens from 200 samples were done by routine smear microscopy, culturing, Kirby–Bauer disc-diffusion assay, and double disc synergy test. Results: Thirty percent of samples were culture-positive pointing Escherichia coli, Klebsiella pneumoniae, Pseudomonas Aeruginosa, and Serratia marcescens (51.9%, 36.5%, 9.61%, and 1.92%, respectively). Almost all ESBL producers were found to be multi-drug resistant that includes E. coli (56.6%), K. pneumoniae (36.74%) and P. aeruginosa (6.66%) warranting prompt need of surveillance for effective clinical management. Conclusion: The current study pointed the emergence and incidence of ESBL producing Gram-negative bacilli that are multi-drug resistant and causing UTI among cancer patients.